Applications of Petri Nets in electric power systems - Gonzalez, Guadalupe; Barazarte, Ronald; Gonzalez, Ruben; Escobar, Julio (Central America and Panama Convention (CONCAPAN XXXIV), 2014 IEEE, 2014)
In this article Petri Nets are presented as a viable alternative to the modeling and analysis of electric power systems. First, the formalism of Petri Nets, its symbology and rules of use will be introduced. Additionally, a synthesis of some of the most relevant cases presented in the literature regarding the use of Petri Nets to model the dynamic of power systems will be presented.
In this article Petri Nets are presented as a viable alternative to the modeling and analysis of electric power systems. First, the formalism of Petri Nets, its symbology and rules of use will be introduced. Additionally, a synthesis of some of the most relevant cases presented in the literature regarding the use of Petri Nets to model the dynamic of power systems will be presented.
Keywords: smart grids; Distribution systems; Petri Nets; power systems; smart grids; Distribution systems; Petri Nets; power systems